Doctor's Perception And Prescription Of Oral Contraceptives: A Social Marketing Study In Bangladesh - Mamun, Muhammad Ziaulhaq (Asian Academy of Management (AAM), 2004)
Doctor's perception of oral contraceptive products is very important for social marketing. Though the obvious and important use of oral contraceptives is to prevent unwanted pregnancy, it is also found that awareness regarding non-contraceptive health benefit use of oral contraceptives is increasing. As oral contraceptives have a lot of side effects, normally doctors go for low dose pills to avoid inconvenience and risk when prescribing a patient. In many cases, doctors give their own judgment on the basis of a number of factors in defining low dose pills. It is evident that Nordette 28 and Marvelon are considered to be almost near considering the attributes – less side effect, low dose, reasonable price and patient's preference. Femicon is separated from the rest of the group due to its low price and is perceived by the doctors as the least quality oral contraceptive. Doctors usually like to prescribe Ovostat and Marvelon to those patients who have more purchasing ability and considers price as a quality factor.